Vortical structures for nanomagnetic memory induced by dipole-dipole interaction in monolayer disks. (May 2018) - Liu, Zhaosen; Ciftja, Orion; Zhang, Xichao; Zhou, Yan; Ian, Hou
Abstract: It is well known that magnetic domains in nanodisks can be used as storage units for computer memory. Using two quantum simulation approaches, we show here that spin vortices on magnetic monolayer nanodisks, which are chirality-free, can be induced by dipole-dipole interaction (DDI) on the disk-plane. When DDI is sufficiently strong, vortical and anti-vortical multi-domain textures can be generated simultaneously. Especially, a spin vortex can be easily created and deleted through either external magnetic or electrical signals, making them ideal to be used in nanomagnetic memory and logical devices. We demonstrate these properties in our simulations. Graphical abstract: We find in simulations that, magnetic vortices induced by the DDI show no chirality, the multi-vortex structures simulated with two quantum methods agree well with each other, both external magnetic field and uniaxial anisotropy perpendicular to the disk-plane can help stabilize the vortical textures if DDI is not strong enough, providing new techniques for nanomagnetic data storage and computing.Image 1 Highlights: Two quantum computational approaches are employed in the present work. The multi-vortex structures obtained with the two methods agree well with each other. There, vortices and anti-vortices emerge simultaneously to minimize the total energy. External magnetic or uniaxial anisotropy can help induce vortical magnetic structure. Our findings provide new techniques to make nanomagnetic storage and logical devices.